Implementasi Strategi Manajemen Dalam Konteks Pelestarian Budaya - Nanang Koswara (Kontigensi : Jurnal Ilmiah Manajemen, 2017)
The purpose of this study is to analyze and give the input of strategy implementation of management, consist of: program, budget, procedure. 1) To analyze the program arrangement and implementation in cultural conservation. 2) To analyze the budgeting arrangement and implementation that stated by the Statement of Governor of West Java. 3) To analyze the procedure between the sector of culture of Regency/City of The tourism and culture departement, the Cultural Community and Stakeholder in the activity. The study used qualitative analysis approach with the single case study. There are 8 (Eight) key informants defined by certain criteria. Those are: The 4 (Four) key informants of Cultural Community as external and the 4 (Four) key informants of Cultural Manager as internal. From the collection and analysis of data and information can be seen that: 1) As guidance and a basis of program arrangement and implementation of cultural conservation, the tourism and culture departement has done the activities according to people expectations. Although there are many cultural product and people expectations and the bounded regulations, The Tourism and culture department of West Java has not been optimal facilitated yet. 2) The method of budgetting arrangement and implementation that stated by the Statement of Governor of West Java is still used as a basis to determine a budget, because the statement of budgetting is not absolutely an authority of The tourism and culture departement. But in order to be optimal, The Statement of Governor of West Java must be specifically separated, that is The Statement of Budgeting and Cultural Management. 3) The procedure has been done between the sector of culture of Regency/City of the Tourism and Cultural Departement, cultural community, and the stakeholder in doing the activities. It has been done according to expectations of the part of cultural community.